Effect of Zn(S, O, OH) Buffer Thin Films Formed on CIGS through Different Stages and Reaction Processes in Chemical Bath Deposition: Interpretations from Mechanisms and Transformation Kinetics Perspective. Issue 7 (12th April 2022) - Cho, Ara; Ostrysz, Marlena; Song, Soomin; Shin, Donghyeop; Jeong, Inyoung; Eo, Young-Joo; Ahn, Seung Kyu; Kim, Kihwan; Park, Joo Hyung
Abstract : Herein, Zn(S, O, OH) is used as a buffer material for Cu(In, Ga)Se2 (CIGS) solar cells instead of CdS to increase the quantum efficiency and remove toxicity. To control the fine thickness of the Zn(S, O, OH) thin films in the chemical bath deposition (CBD) method, a quartz crystal microbalance (QCM) system is introduced by measuring the frequency change. As the frequency changes are adjusted according to the S/O ratio of the Zn(S, O, OH) buffer (Zn buffer) produced during the reaction, the formed phase and thickness are cross‐validated several times to obtain the accurate thickness. These different S/O ratios can be modified by different deposition mechanisms and reaction processes depending on the reaction rate of material formation. Therefore, to investigate the associated mechanism and reaction process in detail, Zn buffer thin films are formed and characterized using two different Zn sources (zinc sulfate and zinc acetate) that affect the reaction rate due to the anion effect. In addition, the optimal deposition range is obtained by comparing the performances of the solar cells with Zn thin films of the same thickness, deposited through different stages in a continuous CBD reaction. Finally, the effect of Zn buffers using different Zn sources on the interfaces with CIGS is investigated in the band alignment. Abstract : This is a schematic diagram of the Zn buffer thin film formation process with different properties due to anion shape and pH. The interface between Cu(In, Ga)Se2 (CIGS) and these Zn buffer thin films has different band structures, showing different performance of solar cells. These results are interpreted using the mechanism and transformation kinetics, and these interpretations are verified through analysis.